Rekonstruksi Model Pengembangan Wisata Sawah Berbasis Sustainability ECOS di Desa Sipaku Area - Kurnia Abdik Nasution, Rahmad; Sitti Nurlaeli; Femmy Indriany Dalimunthe (Journal of Management and Creative Business, 2026)
This study aims to reconstruct a sustainable rice field tourism development model using the Ecotourism Opportunity Spectrum (ECOS) framework in Sipaku Area Village, Asahan Regency. The research is motivated by the underutilization of rural tourism potential and the absence of an integrated model that balances environmental, social, economic, and institutional dimensions. A mixed-method approach was employed through in-depth interviews, field observations, and surveys involving local communities and stakeholders. The findings reveal that although the village possesses strong potential in terms of natural landscape, agricultural activities, and social capital, the current development remains fragmented and lacks institutional and environmental management integration. This study reconstructs a Sustainability ECOS model that integrates environmental sustainability, community participation, organizational governance, and sustainable economic development. The proposed model provides a structured and applicable framework for managing rice field tourism in a sustainable manner. The study contributes theoretically by extending the ECOS framework into an operational model and practically by offering strategic guidance for policymakers and local stakeholders in developing sustainable rural tourism.